The Transformative Impact of AI on Modern System Integration - Narendra Maddukuri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of Artificial Intelligence on modern system integration, exploring how AI technologies are revolutionizing how organizations connect and manage their enterprise applications. The article investigates the core AI technologies driving this transformation, including supervised learning, unsupervised learning, and reinforcement learning algorithms, and their applications in data mapping, error handling, and API management. The article demonstrates how AI-enabled integration platforms significantly improve operational efficiency, security, and scalability by analyzing implementation strategies, technical architectures, and best practices. The findings reveal that organizations implementing AI-driven integration solutions experience substantial reductions in deployment time, enhanced data accuracy, and improved system reliability while maintaining robust security and compliance frameworks. The article also highlights the importance of structured change management approaches and proper architectural considerations in successful AI integration implementations.
Keywords: Artificial Intelligence Integration; Enterprise System Integration; Machine Learning Algorithms; Integration Platform Architecture; Digital Transformation Automation